The Significance Of Spatial Factors In Influencing The Price Of Heritage Properties In George Town, Penang - Soon, Lam Tatt (2010)
The aim of this research is to determine the significance of selected spatial factors and the influence of these spatial factors on heritage property prices in George Town 1. Spatial factors related to location, neighbourhood and local amenities such as transportation points, highway, shopping centre and school are tested in this research. Hedonic regression analysis is used to study the relationship between spatial factors and heritage property price in George Town 1. A total of 231 heritage property transaction records from year 1998 to 2004 are used in this analysis.